2020
DOI: 10.1053/j.ackd.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Medication Use in Kidney Disease

Abstract: Pregnancy in CKD is a condition fraught with challenges including multiple medications, high-risk pregnancy followed by maternal and fetal compromise such as preterm delivery, and low birth weight infant. Breastfeeding is unique in its impact on the mother and the baby, their bonding, and future health implications impacting the society. Breast milk is produced specific for the infant by the biological mother. It changes in composition with lactation stage and leads to optimal growth of the baby including esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Breastfeeding in KFRT is challenging, not only due to the impact of the hemodialysis procedure but also due to the adverse effects of drugs on infants and lactation itself. Experts also raise concerns about the mother's ability to feed her baby, given her clinical condition after a complicated, high-risk pregnancy (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding in KFRT is challenging, not only due to the impact of the hemodialysis procedure but also due to the adverse effects of drugs on infants and lactation itself. Experts also raise concerns about the mother's ability to feed her baby, given her clinical condition after a complicated, high-risk pregnancy (4).…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary and nutritional perspective, exclusive breastfeeding during the first 6 months of life has been recognized as the gold standard of infant nutrition (2). The benefits and indispensability of breastfeeding for the harmonious development of the child have been confirmed by numerous studies (3)(4)(5). Milk promotes optimal growth of the child, including the establishment of circadian rhythms, the production of protective antibodies, and the formation of a healthy gut microbiome (6).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Survei Nasional 2016, tingkat pemberian ASI eksklusif di kalangan wanita selama bulan pertama setelah melahirkan mencapai 66,2%, menunjukkan hasil yang memuaskan (Chu, Sheu, Hsu, Liao, & Chien, 2019). Menyusui adalah tantangan, unik dalam dampaknya pada ibu dan bayi, ikatan mereka dan implikasi kesehatan di masa depan yang berdampak pada perilaku baik di masyarakat (Singh, 2020).…”
Section: Pendahuluanunclassified
“…Breast milk is an ideal food for the healthy growth and development of infants. Studies have shown that the bene ts of breastfeeding include but are not limited to: the reduction of childhood infections (upper respiratory disease, otitis media, and gastroenteritis) and allergies, higher cognitive function and improved neurocognitive [1][2][3] in newborns, of importance to the growth, active and passive immunity, the establishment of circadian rhythms, as well as cognitive and psychosocial development among newborns. [4] However, some drugs can affect the infant through breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, drugs with a short half-life period, strong protein binding capacity, low oral bioavailability to infants, high molecular weight, and relative infant dose (RID) of less than 10% are safe for breastfed infants. [3,5,6] The nal dose encountered by an infant must be determined with respect to both the milk secretion rate and the disposition of the drug in the infant. [5,6] Prolactin (PRL) is a polypeptide hormone synthesized and released from the anterior pituitary gland that regulates lactation, reproduction, metabolism, immune responses, and electrolyte balance.…”
Section: Introductionmentioning
confidence: 99%